The Role of Financial Technology (Fintech) in Financial Inclusion and MSME Growth in Indonesia - Adrian Eka Darma Serang; Ummy Kalsum; Yunior Pasagi; Eka Lestari Hafqi Putri (Oikonomia : Journal of Management Economics and Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy with significant contributions to GDP and employment. However, their access to formal financial services is still limited due to strict requirements from conventional financial institutions and high levels of business informality. Financial technology (fintech) is present as a more inclusive financing alternative through services such as peer-to-peer (P2P) lending and digital payments. Fintech offers fast processes, no collateral, and product flexibility, but its effectiveness is highly dependent on the financial and digital literacy of MSME actors. This study uses a qualitative approach with a case study method in two different regions to explore access, impact, and challenges of fintech use by MSMEs. Initial results show that although fintech expands access to financing and encourages digitalization, there is still a risk of over-indebtedness, inequality in digital infrastructure, and low understanding of contracts and financial obligations. Therefore, synergy is needed between the government, regulators, and service providers to strengthen financial literacy and create a fair and sustainable digital ecosystem. This research is expected to contribute to the development of policies that support the comprehensive digital financial transformation of MSMEs, as well as ensuring that fintech becomes an instrument of empowerment, not a source of new vulnerabilities